Phosphate removal from aqueous solutions by nano-alumina for the effective remediation of eutrophication - Yadav D.; Kumar P.; Kapur M.; Mondal M.K. (My University, 2025)
Excessive phosphate effluent discharged in the surface water source rush to eutrophication. Consecutively this disturbs the water quality and aquatic ecosystem, due to the depletion of dissolved oxygen. Reduced oxygen level in water bodies affects aquatic life and decreases biodiversity. The present investigation emphasized the phosphate adsorption over nano-alumina. Surface characteristics of the adsorbents, BET, FTIR, XRD, TEM, and SEM were analyzed to reveal the phosphate adsorption mechanisms. The adsorption isotherms, kinetics, pH effect were observed in batch experiments. The pH pzc value of nano-alumina adsorbent was found as 8.1. The maximum phosphate adsorption was found to be 98.75% at contact time of 90 min and pH 6. Different models, e.g., Langmuir, Freundlich, Temkin, and Dubinin-Radushkevich were used for isotherm study. The kinetic data were tested by pseudo-first order and second order models. An attempt was made to regenerate the spent adsorbent for reuse in the adsorption process. Low cost and high capability of nano-alumina make it feasible to utilize as cost-effective phosphate remediation from wastewater. © 2018 American Institute of Chemical Engineers Environ Prog, 38: S77–S85, 2019. © 2018 American Institute of Chemical Engineers